An ASSESSMENT OF INNOVATION ACTIVITY ENTERPRISES USING THE MATRIX METHOD - Алиева, Эльнара (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The innovative activity of an enterprise is associated with a high degree of risk. Therefore, the management and organization of innovative activities of an enterprise is accompanied by constant consideration and assessment of all criteria, factors and indicators that influence the efficiency and effectiveness of the activities carried out. The main tools used in assessing innovation activity, taking into account all indicators and indicators, strengths and weaknesses of innovation activity, opportunities and threats, taking into account their strategic significance, risks and expected profitability, include: indicators of innovation activity, financial indicators, key production indicators (KPI), assessment of market reaction, SWOT analysis, use of technological and methodological tools, as well as matrices. These tools help assess important aspects of an enterprise's innovative activities and make informed management decisions for the further development and optimization of the company's innovative potential. The matrix is ​​one of the important tools for assessing the innovative activities of an enterprise. In the context of innovation, it takes into account the various goals of the enterprise and is used to evaluate ideas based on their potential and risks, manage and evaluate indicators and criteria of innovation activity according to various parameters, such as strategic importance, expected profitability, degree of risk and other factors, evaluate types of innovations according to the degree of novelty and breadth of implementation, assessment of the current state and prospects for the development of innovative products at various periods of their life cycle. The use of matrices in assessing innovation activities helps to structure information, facilitates decision-making and improves innovation management in an organization. Each specific matrix can be adapted and customized to suit the unique needs and strategy of the enterprise.